KONTRIBUSI SEKTOR PERTANIAN DALAM PEREKONOMIAN DI KABUPATEN MINAHASA - Nomiles Bembok; Gene Henfried Meyer Kapantow; Leonardus Ricky Rengkung (AGRI-SOSIOEKONOMI, 2020)
This study aims to determine the contribution of the agricultural sector to the economy in Minahasa Regency for the 2014-2018 period. This research was conducted from March to May 2020. The data collection method used secondary data, which was sourced from the Central Statistics Agency of Minahasa Regency, and other sources such as mass media, journals, and other literature that related to this research topic. The variable measured in this study is the Gross Regional Domestic Product (PDRB) of Minahasa Regency at Constant Prices (ADHK) in 2014-2018. Data analysis used descriptive analysis method by making tables and percentages to explain the contribution of the agricultural sector to the economy in Minahasa Regency for the 2014-2018 period. The results showed that the contribution of the agricultural sector to the economy of Minahasa Regency from 2014 to 2018 continued to decline, with an average decline of 0.60% per year. However, the agricultural sector is still the largest contributor to the economy of Minahasa District.*eprm*